Peningkatan Hasil Belajar Pengetahuan Pak Dengan Model PBL Pada Materi “Gereja yang Satu dan Kudus” Kelas VI Fase C - Petrus Efendi; Hartutik Hartutik (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
This research is a Classroom Action Research (PTK) which aims to improve student learning outcomes in the subject of Catholic Religious Education and Ethics through the application of the Problem Based Learning (PBL) learning model. The research was carried out in grade VI of SD Negeri 05 Sekubang in the even semester of the 2024/2025 school year and took place in two cycles. Cycle I will be held on April 7, 2025 with material on the One and Holy Church, while cycle II will be held on April 9, 2025 with material on the Catholic and Apostolic Church. Each cycle consists of four stages: planning, implementation of actions, observation, and reflection. This research method combines qualitative and quantitative approaches. Quantitative data was obtained through formative tests to measure the achievement of students' cognitive learning outcomes, while qualitative data was collected through observation, field notes, and documentation to assess the development of students' affective aspects based on the dimension of the Pancasila Student Profile (P3), especially in the Critical Reasoning dimension. The results of the study showed a significant improvement in the cognitive and affective aspects of students. The average cognitive score increased from 62 in the first cycle to 85 in the second cycle, with learning completeness increasing from 42.11% to 89.47%. In the affective aspect, there was an increase in the number of students who were categorized as "developing according to expectations" and "very developed" in critical thinking skills. In addition, teachers' ability to manage PBL-based learning has also improved, which has an impact on increasing active participation and student learning motivation. In conclusion, the application of the Problem Based Learning (PBL) model has proven to be effective in improving student learning outcomes and character, especially in critical thinking skills. This study recommends that teachers continue to develop skills in implementing PBL and that schools provide full support for the implementation of innovative learning to improve the overall quality of education.